Variation in patients’ perceptions of elective percutaneous coronary intervention in stable coronary artery disease: cross sectional study - Kureshi, Faraz (BMJ Publishing Group Ltd., 2014)
Objectives To assess the perceptions of patients with stable coronary artery disease of the urgency and benefits of elective percutaneous coronary intervention and to examine how they vary across centers and by providers. Design Cross sectional study. Setting 10 US academic and community hospitals performing percutaneous coronary interventions between 2009 and 2011. Participants 991 patients with stable coronary artery disease undergoing elective percutaneous coronary intervention. Main outcome measures Patients’ perceptions of the urgency and benefits of percutaneous coronary intervention, assessed by interview. Multilevel hierarchical logistic regression models examined the variation in patients’ understanding across centers and operators after adjusting for patient characteristics, using median odds ratios. Results The most common reported benefits from percutaneous coronary intervention were to extend life (90%, n=892; site range 80-97%) and to prevent future heart attacks (88%, n=872; site range 79-97%). Although nearly two thirds of patients (n=661) reported improvement of symptoms as a benefit of percutaneous coronary intervention (site range 52-87%), only 1% (n=9) identified this as the only benefit. Substantial variability was noted in the ways informed consent was obtained at each site. After adjusting for patient and operator characteristics, the median odds ratios showed significant variation in patients’ perceptions of percutaneous coronary intervention across sites (range 1.4-3.1) but not across operators within a site. Conclusion Patients have a poor understanding of the benefits of elective percutaneous coronary intervention, with significant variation across sites. No sites had a high proportion of patients accurately understanding the benefits. Coupled with the wide variability in the ways in which hospitals obtain informed consent, these findings suggest that hospital level interventions into the structure and processes of obtaining informed consent for percutaneous coronary intervention might improve patient comprehension and understanding.